Strategi Peningkatan Pendapatan Asli Daerah (PAD) Melalui E-SPTPD (Surat Pemberitahuan Pajak Daerah Berbasis Elektronik) di Kota Surabaya - Putri, Cheryll Nandissya Aulya; Almuqita, Arinda Qomarin; Fanida, Eva Hany; Fitrie, Revienda Anita (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the optimisation of local tax revenue in the City of Surabaya based on data sourced from local policy documents, local government financial reports, and official publications by the Regional Revenue Agency. The research findings indicate that local tax revenue has shown consistent growth and makes a significant contribution to local own-source revenue. This growth is primarily driven by the implementation of the e-SPTPD digital tax system, which has improved administrative efficiency, reporting transparency, and taxpayer compliance, particularly within the trade and services sectors. Other key findings indicate that tax digitalisation not only accelerates service processes but also expands the scope of oversight and the tax compliance base. However, optimisation still faces challenges in the form of low digital literacy among taxpayers, limited human resource capacity, as well as sub-optimal inter-agency integration and overlapping regulations. Consequently, strengthening digital tax literacy, enhancing the competence of civil servants, and cross-agency system integration are key factors in ensuring the sustainability of local revenue growth. Thus, the optimisation of local taxation relies not only on digital systems but also on institutional readiness and public adaptation to the transformation of public services.